Liquid radial flows with a vortex through porous media - Yuri P. Rybakov; Natalia V. Semenova (Discrete and Continuous Models and Applied Computational Science)
The filtration process is studied for a popular class of filters with radial cartridges that proved their high effectiveness in purification of water. The mass balance equation for radial flows in porous media is obtained by using the lattice approximation method, the transverse diffusion process being taken into account. The Euler dynamical equations are modified by including the Darcy force proportional to the velocity of the filtration flow. The system of equations is written for the stationary axially symmetric radial flow and solved by the perturbation method, if the vertical velocity is supposed to be small.